(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to gender equality. It analyzes the issues of social protection of women, measures taken, in particular, in the Republic of Uzbekistan and the solution of the upcoming tasks of ensuring their active participation in the economic, political, social and cultural life of society in the process of globalization taking place in the world.